Impact of Housing Provision Package on Treatment Outcome Among Homeless Tuberculosis Patients in South Korea. (October 2019) - Kim, Hyunwoo; Choi, Hongjo; Yu, Sarah; Lee, An-Yeol; Kim, Hye-Ok; Joh, Joon-Sung; Heo, Eun Young; Oh, Kyung-Hyun; Kim, Hee Jin; Chung, Haejoo
The objective of this study was to assess the effect of a housing provision package on treatment outcomes among homeless South Korean tuberculosis (TB) patients. We conducted a prospective, single-arm, community-based study with historical controls as follows: community-based intervention group (COM), who were provided housing, nutrition, and case management, and received directly observed therapy services; a first historical control that was treated as usual (TAU); and a second historical control that comprised homeless TB patients residing in long-term TB-care facility (FAC). A multivariable logistic regression model was constructed to identify predictors associated with treatment success among homeless TB patients. Treatment was successful in 86.0%, 58.3%, and 96.1% of patients in the COM, TAU, and FAC groups, respectively. Interventions, including those found in the COM and FAC groups, were the only predictors of treatment success. Therefore, we determined that housing provision package positively influenced the treatment outcomes of homeless TB patients.